2011
DOI: 10.1007/978-94-007-2063-3_8
|View full text |Cite
|
Sign up to set email alerts
|

Representing Grounding Line Dynamics in Numerical Ice Sheet Models: Recent Advances and Outlook

Abstract: Recent satellite observations of the Antarctic and Greenland ice sheets show accelerated ice flow and associated ice sheet thinning along coastal outlet glaciers in contact with the ocean. Both processes are the result of grounding line retreat due to melting at the grounding line (the grounding line is the contact of the ice sheet with the ocean, where it starts to float and forms an ice shelf or ice tongue). Such rapid ice loss is not yet included in large-scale ice sheet models used for IPCC projections, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…In simple equilibrated flow-line tests, this means that the model flux equals the net surface mass balance upstream from the grounding line, an important property of analytic solutions. This yields good agreement with analytic solutions including hysteresis in MISMIP-like tests, using grid sizes of ∼ 5 to several 10s km Docquier et al, 2011;Pattyn et al, 2012a). The agreement can be made almost exact by adjusting the flux q g for the increment in surface mass balance between the actual grounding line and the point where Eq.…”
Section: Grounding-line Flux Conditionsupporting
confidence: 64%
“…In simple equilibrated flow-line tests, this means that the model flux equals the net surface mass balance upstream from the grounding line, an important property of analytic solutions. This yields good agreement with analytic solutions including hysteresis in MISMIP-like tests, using grid sizes of ∼ 5 to several 10s km Docquier et al, 2011;Pattyn et al, 2012a). The agreement can be made almost exact by adjusting the flux q g for the increment in surface mass balance between the actual grounding line and the point where Eq.…”
Section: Grounding-line Flux Conditionsupporting
confidence: 64%
“…Alternative mathematical approaches (Katz and Worster, 2010), numerical experiments, and model inter-comparisons (Docquier et al, 2011;Pattyn et al, 2012;Drouet et al, 2013) have confirmed the basic accuracy of the Schoof (2007) formula and approach. However, models incorporating the full set of appropriate mechanical equations predict flow across the grounding line up to twice as fast as given by the Schoof formula (e.g.…”
mentioning
confidence: 71%
“…Recent years have seen a focus on improving the modelling accuracy of marine ice-sheets, where the bed is substantially grounded below sea level (Hindmarsh, 2006;Schoof, 2007;Katz and Worster, 2010;Nick et al, 2010;Docquier et al, 2011;Drouet et al, 2013;Feldmann et al, 2014). The grounding line is where ice, flowing from its source areas, begins to float.…”
Section: Improvements In Modelling Marine Ice Sheet Grounding Linesmentioning
confidence: 99%
“…This failure has been clearly illustrated by Vieli and Payne (2005) and Docquier et al (2011). On the other hand, models that implement melting at the grounding line, i.e., the last grounded grid point, melt grounded ice away, thereby mimicking grounding line retreat.…”
Section: Grounding Line Migration In the Searise Ensemblementioning
confidence: 99%